National Household Education Survey, 1995 ([Verlag nicht ermittelbar], 1998)
The National Household Education Survey (NHES) series reports information on the condition of education in the United States by collecting data at the household level rather than using a traditional school-based data collection system. The surveys attempt to address many current issues in education, such as preprimary education, school safety and discipline, adult education, and activities related to citizenship. This survey includes two topical survey components: the Adult Education (AE) component, which collected information about adults' participation in adult education, and the Early Childhood Program Participation (ECPP) component, which focused on children's participation in nonparental childcare and early childhood programs. The AE component explored the participation of adults (aged 16 years and older) in a wide range of educational activities during the 12 months prior to the interview. Respondents were asked about their participation in seven broadly-defined types of adult education activities: adult basic skills and GED preparation classes, English As a Second Language instruction, courses taken toward college degrees or vocational diplomas or certificates, apprenticeship programs, career or job-related courses, any other formally structured courses, and computer-only or video-only instruction on the job. The AE component also collected data pertaining to reasons for and barriers to participation in adult education. In all, 19,722 adult interviews were completed: 11,713 with adult education participants and 8,009 with nonparticipants. The ECPP component examined children's early experiences in various types of nonparental childcare arrangements and early childhood programs. The core of this survey collected extensive information on children's participation and experiences in four types of nonparental care and programs: care by relatives (not including parents), care by nonrelatives, Head Start programs, and other center-based programs. Other information collected in this component concerned children's kindergarten and primary school experiences, children's personal and household demographic characteristics, parent/guardian characteristics, literacy-related home activities, and children's health and disability status. In total, interviews were completed for 14,064 children who were newborn through age 10 and in 3rd grade and below. This includes interviews for 4,135 infants and toddlers, 3,431 preschool children, 1,680 kindergarten children, 4,717 primary school children, and 101 home-schooled children.